KEBERLANGSUNGAN AGENSI KREDIT MIKRO DALAM MEMBANGUN PEDAGANG KECIL : BAITUL MAL WAT-TAMWIL DI PROVINSI RIAU - KHAIDIR SAIB (Universitas Islam Negeri Imam Bonjol Padang, 2016)
One of the micro-finance agency, is Baitul Mal wat-Tamwil considered as Islamic micro finance agencies that can provide financial services to people with low income. Islamic micro finance agencies in the past have always shown considerable achievements in terms of quantity, the contribution of the absorption of labour power to the gross national income, so that efforts to empower communities through the development of its own capabilities and social and economic institutions that can reach and serve more communities business unit that cannot be reached directly by the general banking or Islamic banking. Looking a t the development effort, it is necessary to network better security, so that the existence of Baitul Mal wat-Tamwil increasingly powerful, healthy and sustainable. The methodology used in this study qualitative approach. This study shows that there are some factors that affect the sustainability of the BMT finesse Access Capital, Ability to resolve problems installment payment, strict control function, Employee Collaboration (teamwork), willing and Challenges Facing obstacles and Supply of Human Resources.